A regionalized historical-sociological constitutionalist analysis of the right to basic education in the district of Bailique in Macapá-AP: The education that Brazil does not know and does not need - Gonçalves, Wanny Lobato; Rodrigues, Regiane Guedes; Furlan, Donizete Vaz (Seven Editora, 2023)
The first manifestation regarding public education was registered in 1717, the year in which the King of Prussia instituted compulsory primary education in his country for children from 05 to 12 years old. In Brazil, the first Constitution granted by Dom Pedro, in 1824, recognized the right to education. In his text, he presented the free primary education for all citizens among civil and political rights, but selective, not extending this right to the entire population. Currently, the right to education is provided for in article 205 of the 1988 Federal Constitution. It is a right of all and a duty of the State. However, as much as this right is provided for in our legal system, many localities face numerous difficulties, some more and some less, in access to education, as is the case of the district of the Bailique Archipelago, located in the State of Amapá, about 230 km from the capital Macapá. The difficult access to the region corroborates its "oblivion" by the government and consequent violation of rights. People living in situations of social exclusion do not have the guarantee of access to or attendance at school, for example, with special emphasis on children and adolescents. Such violations contribute to perpetuating the intergenerational cycle of social inequality and poverty. DOI:https://doi.org/10.56238/sevened2023.006-018